Correlation of Pain Reduction with fMRI BOLD Response in Osteoarthritis Patients Treated with Paracetamol: Randomized, Double-Blind, Crossover Clinical Efficacy Study. Issue 2 (29th August 2017) - Yue, Yong; Collaku, Agron
Abstract: Objective: To assess the relationship between the analgesic efficacy of extended-release paracetamol (ER-APAP) and brain blood oxygen level–dependent (BOLD) signal activation in response to painful stimulation measured by functional magnetic resonance imaging (fMRI) in patients with osteoarthritis of the knee. Methods: This placebo-controlled, double-blind, crossover, randomized trial (N = 25) comprised three treatment periods in which patients received four doses of an eight-hour ER-APAP caplet (2 x 665 mg), four doses of matched placebo, and no treatment. Pain intensity of the knee was measured before and after painful stimulation at the knee with osteoarthritis and before and after fMRI. Results: ER-APAP significantly reduced prestimulation osteoarthritis knee joint pain compared with baseline ( P < 0.003) and placebo ( P < 0.004). ER-APAP and placebo significantly reduced knee joint pain after stimulation ( P = 0.014 and P = 0.032, respectively); however, pain reduction with ER-APAP was 35% greater than placebo. ER-APAP was associated with significant reductions in BOLD signal activation after stimulation compared with control in the sensory cortex ( P = 0.002) and supramarginal gyrus ( P = 0.003). Reduction in BOLD signal activation after stimulation for placebo was significantly greater than control in the subgenual prefrontal cortex ( P < 0.001), frontal cortex ( P < 0.001), insula ( P < 0.003), and sensory cortex ( P < 0.001). Conclusions: ER-APAP had a significantly greater effect than placebo and no treatment in reducing knee pain, which was associated with reduced BOLD signal activations in pain pathways, including the sensory cortex and supramarginal gyrus. BOLD observations after placebo treatment may shed light on the role of the brain regions potentially involved in placebo response in clinical trials investigating pain therapies.